Correlation vitamin D [25(Oh)D3] with neutrophil-lymphocyte ratio (NLR) and C-reactive protein (CRP) in cervical cancer patient - Mi’raj, Nurlailah; Rahayu, Muji; Retnoningrum, Dwi; Rachmawati, Banundari; Kurnia Setiawan Limijadi, Edward (Edelweiss Applied Science and Technology, 2024)
Vitamin D [25(OH)D3] levels are currently associated with clinical inflammatory markers such as C-reactive protein (CRP) and neutrophil-lymphocyte ratio (NLR). They are used to monitor the development of cervical cancer. Aim of this study was analyze the correlation of vitamin D [25(OH)D3] levels with NLR values and CRP levels in cervical cancer patients. Vitamin D is expected to be an alternative treatment for cervical cancer. This study was analytical observational with a cross-sectional design conduct at Dr. Kariadi Hospital Semarang in January-March 2024. [25(OH)D3] level was measured using enzyme-linked immunosorbent assay (ELISA) method, CRP levels were checked with the ADVIA centaur device using the principle of chemiluminescence and combined with immunoassay technology and NLR value was calculated manually. Total sample was 40 cervical cancer patients aged 35-60 years old. Mean±SD results of vitamin D [25(OH)D3] levels, NLR values, and CRP levels were 12.0±5.5 ng/ml; 5.0±1.2; 5.5±2.0 mg/dL. Correlation tests between vitamin D [25(OH)D3] levels with NLR values and CRP levels were sequentially obtained (p=0.036; r=-0.333) and CRP (p=0.000; r=-0.588). Result in this study conclude that Vitamin D [25(OH)D3] levels and NLR values showed a weak negative correlation. A moderate negative correlation exists between vitamin D [25(OH)D3] and CRP level.